LEADERSHIP DALAM PENDIDIKAN ISLAM - Nia Wardhani (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
Every nation is seemed to be qualified to have quality and leadership which can create more dynamic solidarity and unity. It aims at having capability to persist in various competitions and even it is expected to create more competition and superiority. It is also means in the context of broader community, which every nation is demanded to take part actively and positively either in national, regional or international. But it should keep in mind that in every process of leadership, we will always face the chain which is complete from top to down or even to side to side. Thus, understanding and development in the view and perspective of leadership are important to improve strategy and competition. Especially to create national quality and productivity which are full of solidarity and unity.